Is oestrogen associated with mandibular condylar resorption? A systematic review. Issue 11 (November 2017) - Nicolielo, L.F.P.; Jacobs, R.; Ali Albdour, E.; Hoste, X.; Abeloos, J.; Politis, C.; Swennen, G.
Abstract: A systematic review of the literature was performed regarding the influence of oestrogen on the occurrence of mandibular condylar resorption. Search terms for oestrogen were used in combination with terms related to the effect on condylar remodelling. A search of the PubMed, Embase, and Cochrane Central Register of Controlled Trials databases yielded 419 articles published between October 1993 and March 2017. An additional 48 articles were retrieved through manual searching of the reference lists. After initial abstract selection, 94 eligible articles were screened in detail, resulting in a final number of 33 articles included in the review. From this review, no evidence was found that oestrogen (deficiency) contributes to mandibular condylar resorption. The conclusions are limited by the lack of studies with a high level of evidence. Further investigations on serum oestrogen concentrations in women with condylar resorption are needed. Moreover, future studies should focus on the effects of the different types of medication and diseases influencing oestrogen concentrations, the utility of oestrogen concentrations during preoperative screening, and the policies for managing orthognathic surgery patients with an oestrogen deficiency. Finally, whether the mechanisms and risk factors that lead to idiopathic condylar resorption are the same in condylar resorption following orthognathic surgery remain to be elucidated.